GAYA KEPEMIMPINAN KYAI LUKMAN AL-KARIM DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM (Studi Kasus di Pondok Pesantren Bahrul Maghfiroh Malang) - Rusmini, Rusmini (Analisis: Jurnal Studi Keislaman, 2015)
LEADERSHIP    STYLE   OF   KYAI   LUKMAN   AL-KARIM IN THE DEVELOPMENT OF ISLAMIC EDUCATIONAL INSTITUTION:  A CASE STUDY IN PESANTREN  BAHRUL MAGHFIRAH, MALANG: The leadership is not something that can only  be learned  and researched.  Even  in leadership,  many types can be found; character  and the most protrude  leadership action from a person who has an important role in his achievement to  lead  his  institution.  This  research  was  conducted  through field research using qualitative  model. Researcher inspected  the opinions of Kyai Lukman thinking  in his efforts to develop and advance his pesantren. The result of this research is: to lead and defend the existence  of his Islamic boarding school that he runs by himself, Kyai Lukman applies many strategies as follow: First, Kyai  Lukman’s  strategy  in managing  the  educational  funding. Kyai Lukman uses several kinds of method to fund the educational activities in his institution; they are self-funding and donation from the income of pesantren profit centers. Kyai Lukman increases the quality  of laborers in pesantren  Bahrul Maghfiroh by giving the examplary  attitude  of wara‘,  uswatun  hasanah  (good example) and riyadloh (tirokat)  to all students, all laborers and all teachers (asatizh). Kyai Lukman also expanded the curriculum of teaching in his pesantren. Second, the types of Kyai Lukman’s leadership. From many perceptions,  the researcher could classify that  Kyai Lukman has charismatic,  transformational, and visionary leader attitude.